A New Perspective to Measuring Interdependence among Stock, Oil and Currency Markets: A Canonical Correlation Analysis - Idowu Oluwasayo Ayodeji (Indonesian Journal of Statistics and Applications, 2022)
With a view to explaining various seemingly-contrasting results often reported in financial linkages literature, the study investigates the possibility of the existence of more than one unique relationship among stock, oil and currency markets. It also quantified the impact of selected macroeconomic variables on these relationships. Three prominent markets of stock, oil and exchange rates were examined from the United States, United Kingdom and Nigeria. The model adopted was the canonical correlation specification. Canonical solution identified two significant unique association patterns each among US, UK and Nigerian markets, indicating that their linkages vary with time. We also observed that the effect of macroeconomic variables on the link among financial markets vary by country and data frequency. Overall, inflation rates played the most significant role in the linkages among financial markets. The study concluded that the previous results on interdependence among financial markets are not conflicting but rather complimentary as they evidenced the multiple patterns of association among markets.